2013
DOI: 10.1021/nl402797j
|View full text |Cite
|
Sign up to set email alerts
|

The Backside of Graphene: Manipulating Adsorption by Intercalation

Abstract: The ease by which graphene is affected through contact with other materials is one of its unique features and defines an integral part of its potential for applications. Here, it will be demonstrated that intercalation, the insertion of atomic layers in between the backside of graphene and the supporting substrate, is an efficient tool to change its interaction with the environment on the frontside. By partial intercalation of graphene on Ir(111) with Eu or Cs we induce strongly n-doped graphene patches throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 57 publications
2
80
1
Order By: Relevance
“…Huang et al [210] found that the rare earth Ce was unusual, in that it intercalated at 300 K, in contrast to 6 other elements studied, Pt, Pd, Ni, Co, Au, and In, which all required heating to 500-800 K, on G1/Ru(0 0 1). It should be noted that by contrast, Schumacher et al found that the rare earth Eu intercalates under G1/Ir(1 1 1) only at elevated temperatures [201].…”
Section: Driving Force and Mechanism For Intercalation And The Intercmentioning
confidence: 93%
See 4 more Smart Citations
“…Huang et al [210] found that the rare earth Ce was unusual, in that it intercalated at 300 K, in contrast to 6 other elements studied, Pt, Pd, Ni, Co, Au, and In, which all required heating to 500-800 K, on G1/Ru(0 0 1). It should be noted that by contrast, Schumacher et al found that the rare earth Eu intercalates under G1/Ir(1 1 1) only at elevated temperatures [201].…”
Section: Driving Force and Mechanism For Intercalation And The Intercmentioning
confidence: 93%
“…While experiments on exfoliated graphene of various thicknesses from single to multilayers have shown that the island density can depend dramatically on the carbon layer thickness for Cs [37] and for Au [16,17], recent experiments also show that metal intercalation [35,185,[199][200][201] provides a way to effectively modify the properties of graphene and tune the adatom bonding. It has been shown that adsorption of metal atoms can be manipulated by the insertion of metallic layers between graphene and the supporting substrate [201].…”
Section: Effect Of Intercalation On Surface Metal Growthmentioning
confidence: 99%
See 3 more Smart Citations